2016
DOI: 10.1186/s40813-016-0037-y
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of piglets at 2 and 3 weeks of age with Ingelvac PRRSFLEX® EU provides protection against heterologous field challenge in the face of homologous maternally derived antibodies

Abstract: BackgroundDue to difficulties in eradicating porcine reproductive and respiratory syndrome (PRRS) linked to biosecurity challenges, transmission of the virus and the lack of efficient DIVA vaccines, successful control of PRRS requires a combination of strict management measures and vaccination of both sows and piglets. The present study aimed to assess the efficacy of a recently developed MLV vaccine (Ingelvac PRRSFLEX® EU) in piglets at 2 and 3-weeks of age in the presence of homologous maternally derived ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
3
17
0
Order By: Relevance
“…Although genetic distance in the ORF5 gene locus is not a stoichiometric indicator of the likelihood of protection, the protection demonstrated in this study with the chosen genetic distance of less than 87% homology between the vaccine and challenge should provide a good level of assurance that the vaccine could protect against heterologous PRRSV strains. As in previous cases, this should also be verified in field studies [ 27 ].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Although genetic distance in the ORF5 gene locus is not a stoichiometric indicator of the likelihood of protection, the protection demonstrated in this study with the chosen genetic distance of less than 87% homology between the vaccine and challenge should provide a good level of assurance that the vaccine could protect against heterologous PRRSV strains. As in previous cases, this should also be verified in field studies [ 27 ].…”
Section: Discussionsupporting
confidence: 62%
“…Some animals did not test positive by either RT-qPCR or ELISA and showed the same level of protection upon challenge compared with animals that had seroconverted. Incomplete seroconversion alongside full protection from PRRS has already been observed in other studies [ 27 ] and most likely reflects variability in immune responses between animals.…”
Section: Discussionsupporting
confidence: 57%
“…However, challenge-induced viremia reduction was not linked to seropositivity at challenge in any of the studies. Incomplete seroconversion alongside full protection from PRRS has already been described in other studies and most likely reflects the relevant role of the cell-mediated immunity in PRRSV clearance from the blood as well as the variability in immune responses between animals [11,21,22].…”
Section: Discussionsupporting
confidence: 62%
“…This interference of MDNAs with postvaccination immune response suggested weak protection against PRRSV infection of piglets vaccinated in presence of high MDNA levels that could explain the lower vaccine efficacy observed in the field. Previous studies reported that vaccination in piglets with high MDA levels had no impact on vaccine efficacy but neutralizing antibodies (NAs) were not considered [15]. In the present study, piglets were vaccinated in the presence of low or high MDNA levels and further challenged with a wild PRRSV-1 to assess the impact of MDNAs on the efficacy of PRRSV-1 MLV vaccination.…”
Section: Introductionmentioning
confidence: 95%